2021
DOI: 10.3389/fimmu.2021.754961
|View full text |Cite
|
Sign up to set email alerts
|

Serum LAG-3 Predicts Outcome and Treatment Response in Hepatocellular Carcinoma Patients With Transarterial Chemoembolization

Abstract: BackgroundTransarterial chemoembolization (TACE) stands for the most commonly utilized therapy for hepatocellular carcinoma (HCC) worldwide. This study was to explore the potential predictive and prognostic roles of LAG-3 and PD-L1 as serum biomarkers in HCC patients underwent TACE treatment.MethodsA total of 100 HCC patients receiving TACE as well as 30 healthy controls were enrolled in the study. Serum LAG-3 and PD-L1 levels were determined at baseline and 3 day after TACE using enzyme-linked immunosorbent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…26 According to recent studies, high expression of LAG-3 in tumor tissue or serum indicates an unfavorable prognosis in several cancers, including non-small-cell lung carcinoma, melanoma 27 and HCC. 15 Based on the above, the high blood LAG-3 level in patients with HCC is thought to re ect the suppression of T cell activation and possible resistance to ATZ + BV treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 According to recent studies, high expression of LAG-3 in tumor tissue or serum indicates an unfavorable prognosis in several cancers, including non-small-cell lung carcinoma, melanoma 27 and HCC. 15 Based on the above, the high blood LAG-3 level in patients with HCC is thought to re ect the suppression of T cell activation and possible resistance to ATZ + BV treatment.…”
Section: Discussionmentioning
confidence: 99%
“…11,13 Furthermore, effective killing of cancer cells by an anticancer immune mechanism requires the initiation, progression and iterative expansion of a series of stepwise events, referred to as the "cancer immune cycle." 14 The immune-related molecules and cancer immune cycles, such as programmed cell death 1 ligand 1 (CD274), 5 lymphocyte-activation gene 3 (LAG-3), 15 chemokine (C-C motif) ligand 2 (CCL2), 16 CCL4, 16 CCL5, 16 chemokine (C-X-C motif) ligand 1 (CXCL1), 17 CXCL9, 9 CXCL10, 18 CXCL12, 19 CXCL13, 20 C-C motif chemokine receptor 5 (CCR5), 19 interferon gamma (IFNγ), 18 interleukin 6 (IL-6), 6 and IL-8, 18 have been reported to be secreted into the peripheral blood in HCC patients. Therefore, we analyzed the association between serum levels of the immunerelated molecules, CD274, LAG-3, CCL2, 4, 5, CXCL1, 9, 10, 12, 13, CX3CL1, CCR5, IFNγ and IL-6, 8, and objective response (OR) and prognosis with ATZ + BV treatment for HCC.…”
Section: Introductionmentioning
confidence: 99%
“…We found that there was a higher density of PD-L1 + immune cells in tumor tissues of cluster 2, while no differences were observed in LAG-3 + and FGL-1 + cell densities between cluster 2 and other clusters. Previous studies reported that patients with high expression of PD-L1 and low expression of LAG-3/FGL1 had a better prognosis [ 39 ], explaining why cluster 2 had a higher survival. In the future, we will analyze more common immune checkpoints in HCCs to perfect our research results.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, immune checkpoint inhibitors targeting the above-mentioned molecules may be one of the novel therapeutic options for the treatment of HCC. LAG3 is also a predictor of tumor response following therapy for HCC ( Guo et al, 2021 ). We found that the immune-suppressive cytokines like IL10, IL4, TGFB1, TGFB2, and TGFB3 were significantly expressed in patients with high-risk scores.…”
Section: Discussionmentioning
confidence: 99%